Vessel segmentation of retinal image based on pixel specificity and self-adaptive classification strategy - Ping JIANG; Quan-sheng DOU (Tongxin xuebao)
A new vessel segmentation method called specificity and self-adaptive vessel detection(SSVD)was proposed based on pixel specificity and self-adaptive classification strategy,in the beginning pixel specificity was defined,by setting a higher pixel specificity threshold,the main vessel skeleton was extracted; then self-adaptive classification process was implemented,and each of the remaining undetermined pixels acted as an Agent,within a multi-scale threshold range,Agent revised its own status according to the status of its neighbor,so as to complete the classification of the pixels; finally the noise was removed by multi-window noise filtering method.By testing SSVD on DRIVE database,the experiment shows that it is more accurate and efficient than state-of-the-art methods.